Endobronchial Perfluorocarbon Reduces Inflammatory Activity before and after Lung Transplantation in an Animal Experimental Model - Luiz Alberto Forgiarini Junior; Arthur Rodrigo Ronconi Holand; Luiz Felipe Forgiarini; Darlan Pase da Rosa; Norma Anair Possa Marroni; Paulo Francisco Guerreiro Cardoso; Cristiano Feijó Andrade (Hindawi Limited, 2013)
Background. The aim of this study was to evaluate the use of liquid perfluorocarbon (PFC) as an adjuvant substance for lung preservation and assess its role in pulmonary protection after transplantation. Methods. Seventy-two rat lungs were flushed with low-potassium dextran (LPD) solution and randomized into three main groups: control with LPD alone and experimental with 3 (PFC3) and 7 mL/kg (PFC7) of endobronchial PFC instilled just after harvest. Each group was divided into four subgroups according to preservation time (3, 6, 12, and 24 hours). Afterwards, we performed lung transplantation using rat lungs preserved for 12 hours with LPD alone or with 7 mL/kg of endobronchial PFC. Results. There was a significant increase in oxidative stress in the control group at 6 h of cold ischemic time compared with the PFC3 and PFC7 groups. The apoptotic activity and NF-κB expression were significantly higher in the control group compared with the PFC groups at 3, 12, and 24 h of cold preservation. After transplantation, the NF-κB, iNOS, and nitrotyrosine expression as well as caspase 3 activity were significantly lower in the PFC groups. Conclusion. The use of endobronchial PFC as an adjuvant to the current preservation strategy improved graft viability.